Untangling the Integration–Performance Link: Levels of Integration and Functional Integration Strategies in Post‐Acquisition Integration - Wei, Tian; Clegg, Jeremy (Journal of Management Studies, 2020)
AbstractThe integration–performance link created during post‐acquisition integration has defied satisfactory theoretical explanation. To address this gap, we conduct a functional analysis to explore the intermediating mechanisms between the level of integration – which represents the extent of the target firm’s integration with the acquirer – and acquisition performance. We use six in‐depth acquisition case studies in the medical technology industry to develop an integrated model with which to untangle the integration–performance link. First, our model connects the level of integration to specific functional integration strategies, which refer to the approaches acquirers employ to manage functional resources. Second, we identify value creation and value leakage as the two routes through which functional integration strategies impact acquisition performance. Finally, we propose two qualitative measures of acquisition performance: value gap and time delay. Our study suggests that a functional analysis of the integration–performance link may help resolve long‐standing conflicts within the literature.